Call the Midwife : A True Story of the East End in the 1950s - Worth, Jennifer, 1935-2011; Clinical Editor Coates, Terrri (London Phoenix, 2008)
Life in London's docklands in the 1950s was tough. The brothels of Cable Street, the Kray brothers and gang warfare, the meths drinkers in the bombsites-this was the world that Jennifer Worth entered when she became a midwife at the age of twenty-two. Babies were born in slum conditions, often with no running water. Jennifer Worth describes the romance and beauty of the great port of London, the bug-infested tenements, the spectre of disease, the sense of community and the incredible resilience of women who bore more than ten children. Funny, disturbing and moving, Call the Midwife brings to life a world that has now changed beyond measure
Include Illustration
Keywords: England--London -- Midwives -- Worth, Jennifer, 1935-2011